Centro cultural para la recuperación de la memoria agustiniana (2023)
The main purpose of this research is to formulate a project that has a great scope, not only for its architecture and its benefits, but also for its importance, impact on society and its cultural, historical and heritage value in a tourist environment. For a long time, culture and tourism have created a synergy that involves multiple factors such as the economy and cultural dissemination, having a direct relationship with the development of a city, reaching the point of turning these cities into tourist attractions for a long time. , having as a result, a historical and patrimonial wealth, for this reason its economy can depend to a large extent on tourism. San Agustín is a municipality that not only shares all the cultural richness of the department of Huila, but also a historical mysticism that intrigues each feature of the monolithic heritage discovered under its soil.